EFA6 regulates selective polarised transport and axon regeneration from the axon initial segment - Venkat Kanamarlapudi (Journal of Cell Science, 2017)
Central nervous system (CNS) axons lose their intrinsic ability to regenerate with maturity, whilst peripheral (PNS) axons do not. A key difference between these neuronal types is their ability to transport integrins into axons. Integrins can mediate PNS regeneration, but are excluded from adult CNS axons along with their rab11 carriers. We reasoned that exclusion of the contents of rab11 vesicles including integrins might contribute to the intrinsic inability of CNS neurons to regenerate, and investigated this using laser axotomy. We identify a novel regulator of selective axon transport and regeneration, the ARF6 GEF EFA6. EFA6 exerts its effects from a location within the axon initial segment (AIS). EFA6 does not localise here in DRG axons, and in these neurons, ARF activation is counteracted by an ARF-GAP which is absent from the CNS, ACAP1. Depleting EFA6 from cortical neurons permits endosomal integrin transport and enhances regeneration, whilst overexpressing EFA6 prevents DRG regeneration. Our results demonstrate that ARF6 is an intrinsic regulator of regenerative capacity, implicating EFA6 as a focal molecule linking the axon initial segment, signalling and transport.